Analisis Manajemen Pengendalian Penyakit Bercak Daun Coklat Padi Dengan Jadam Wetting Agent Di Kecamatan Panceng Kabupaten Gresik - Fitriyah, Lailatul; Djazuli, Raden Achmad; Agustina, Rohmatin (CV.ITTC INDONESIA, 2025)
Brown leaf spot disease caused by Bipolaris oryzae poses a significant challenge in rice production. The use of synthetic pesticides potentially leads to adverse effects on ecosystems. This study analyzes the efficacy of Jadam Wetting Agent (JWA) as an adjuvant in controlling the disease within the operational area of the Agricultural Extension Center (BPP) in Panceng District, Gresik. The research methodology combines quantitative and qualitative approaches, involving 60 rice farmers as respondents. Results indicate that JWA application effectively reduces infection intensity by 47.04% and increases dry grain yield productivity by 14.53%. The adoption rate of JWA technology remains moderate (46.67%). Factors significantly influencing adoption include education level, land area, knowledge, and farmers' attitudes. In conclusion, JWA represents an effective and environmentally friendly alternative for disease control. A comprehensive extension strategy is necessary to enhance JWA adoption among farmers.